ACIST-FFR Study (Assessment of Catheter-Based Interrogation and Standard Techniques for Fractional Flow Reserve Measurement). (December 2017) - Fearon, William F.; Chambers, Jeffrey W.; Seto, Arnold H.; Sarembock, Ian J.; Raveendran, Ganesh; Sakarovitch, Charlotte; Yang, Lingyao; Desai, Manisha; Jeremias, Allen; Price, Matthew J.
Abstract : Background—: Measurement of fractional flow reserve (FFR) to guide coronary revascularization lags despite robust supportive data, partly because of the handling characteristics of traditional coronary pressure wires. An optical pressure-monitoring microcatheter, which can be advanced over a traditional coronary guidewire, facilitates FFR assessment but may underestimate pressure wire–derived FFR. Methods and Results—: In this prospective, multicenter trial, 169 patients underwent FFR assessment with a pressure wire alone and with a pressure microcatheter over the pressure wire. An independent core laboratory performed quantitative coronary angiography and evaluated all pressure tracings. The primary end point was the bias or difference between the microcatheter FFR and the pressure wire FFR, as assessed by Bland–Altman analysis. The mean difference between the microcatheter and the pressure wire–derived FFR values was −0.022 (95% confidence interval, −0.029 to −0.015). On multivariable analysis, reference vessel diameter ( P =0.027) and lesion length ( P =0.044) were independent predictors of bias between the 2 FFR measurements. When the microcatheter FFR was added to this model, it was the only independent predictor of bias ( P <0.001). The mean FFR value from the microcatheter was significantly lower than from the pressure wire (0.81 versus 0.83; P <0.001). In 3% of cases (95% confidence interval, 1.3%–6.7%), there was clinically meaningful diagnostic discordance, with the FFR from the pressure wire >0.80 and that from the microcatheter <0.75. These findings were similar when including all 210 patients with site-reported paired FFR data. Conclusions—: An optical, pressure-monitoring microcatheter measures lower FFR compared with a pressure wire, but the diagnostic impact appears to be minimal in most cases. Clinical Trial Registration—: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02577484. Abstract : Supplemental Digital Content is available in the text.